2021 European guideline on the management of Mycoplasma genitalium infections. (19th February 2022) - Jensen, J.S.; Cusini, M.; Gomberg, M.; Moi, H.; Wilson, J.; Unemo, M.
Abstract: Mycoplasma genitalium infection contributes to 10–35% of non‐chlamydial non‐gonococcal urethritis in men. In women, M . genitalium is associated with cervicitis and pelvic inflammatory disease (PID) in 10–25%. Transmission of M . genitalium occurs through direct mucosal contact. Clinical features and diagnostic tests: Asymptomatic infections are frequent. In men, urethritis, dysuria and discharge predominate. In women, symptoms include vaginal discharge, dysuria or symptoms of PID – abdominal pain and dyspareunia. Symptoms are the main indication for diagnostic testing. Diagnosis is achievable only through nucleic acid amplification testing and must include investigation for macrolide resistance mutations. Therapy: Therapy for M .genitalium is indicated if M . genitalium is detected. Doxycycline has a cure rate of 30–40%, but resistance is not increasing. Azithromycin has a cure rate of 85–95% in macrolide‐susceptible infections. An extended course of azithromycin appears to have a higher cure rate, and pre‐treatment with doxycycline may decrease organism load and the risk of macrolide resistance selection. Moxifloxacin can be used as second‐line therapy but resistance is increasing. Recommended treatment: Uncomplicated M. genitalium infection without macrolide resistance mutations or resistance testing: Azithromycin 500 mg on day one, then 250 mg on days 2–5 (oral). Second‐line treatment and treatment for uncomplicated macrolide‐resistant M. genitalium infection: Moxifloxacin 400 mg od for 7 days (oral). Third‐line treatment for persistent M. genitalium infection after azithromycin and moxifloxacin: Doxycycline or minocycline 100 mg bid for 14 days (oral) may cure 40–70%. Pristinamycin 1 g qid for 10 days (oral) has a cure rate of around 75%. Complicated M. genitalium infection (PID, epididymitis): Moxifloxacin 400 mg od for 14 days. Main changes from the 2016 European M. genitalium guideline: Due to increasing antimicrobial resistance and warnings against moxifloxacin use, indications for testing and treatment have been narrowed to primarily involve symptomatic patients. The importance of macrolide resistance‐guided therapy is emphasised.